Analysis of the use of digital technologies in state and municipal government - N. A. Solopova; Zh. V. Selezneva (Vestnik MGSU)
Introduction. The issues of digital technologies (DT) application in state and municipal government are analyzed in the article. The progress made in the field of digital transformation of state and municipal government is considered, the main recommendations for the improvement of this process are formulated.Materials and methods. The theoretical and methodological basis was provided by the scientific works of Russian and foreign scientists devoted to the study of the use of DT in the state and municipal government. Data of Rosstat, Ministry of Digital Development of Russia, abstract and citation database Scopus, as well as the works of Institute for statistical studies and economics of knowledge of National Research University “Higher School of Economics” were used as the materials of the research.Results. The conducted analysis of the practice of digital technologies application in state and municipal government proved that such technologies are actively used in Russia. Besides, the cost of interaction of citizens and the state in this format is twice as cheap as in the traditional face-to-face format. During the pandemic, the pace of digitalization of the state sector accelerated significantly. Electronic payment systems, open data and government portals, information management systems and electronic document management can serve as examples of the use of digital technologies in state and municipal government. Digital technologies give the government the opportunity to provide citizens and businesses with various services and online services, to automate and optimize various processes in state and municipal government, to actively provide access to information required by users. All this contributes to increasing the transparency of the activities of the authorities. Digital technologies allow to improve decision-making in state and municipal government through the use of analytical tools and forecasting methods.Conclusions. Despite the identified shortcomings and problems, it is concluded that, on the whole, the prospects for the development of the use of digital technologies in state and municipal government in Russia is very optimistic and have essential potential.